Livestock Network Analysis for Rhodesiense Human African Trypanosomiasis Control in Uganda - Okello, Walter O.; Amongi, Christine A.; Muhanguzi, Dennis; MacLeod, Ewan T.; Waiswa, Charles; Shaw, Alexandra P.; Welburn, Susan C. (Frontiers in Veterinary Science, 2021)
Background Infected cattle sourced from districts with established foci for T. b. rhodesiense Human African trypanosomiasis (rHAT) migrating to districts previously unaffected by rHAT have resulted in a significant expansion of the rHAT focus in Uganda. This study explores livestock movement data to describe cattle trade network topology and assess the effects of disease control interventions on the transmission of rHAT infectiousness. Methods Network analysis was used to generate a cattle trade network with livestock data which was collected from cattle traders (n=197) and validated using random graph methods. Additionally, the cattle trade network was combined with a susceptible, infected, recovered (SIR) compartmental model to simulate spread of rHAT (Ro 1.287), hence regarded as ‘slow’ pathogen, and evaluate the effects of disease interventions. Results The cattle trade network exhibited low clustering coefficient (0.5) with most cattle markets being weakly connected and a few being highly connected. Also, analysis of the cattle movement data revealed a core group comprising of cattle markets from both eastern (rHAT endemic) and northwest regions (rHAT unaffected area). Presence of a core group may result in rHAT spread to unaffected districts and occurrence of super spreader cattle market or markets in case of an outbreak. The key cattle markets that may be targeted for routine rHAT surveillance and control included Namutumba, Soroti and Molo all of which were in south east Uganda. Using effective trypanosomiasis such as integrated cattle injection with trypanocides and spraying can sufficiently slow the spread of rHAT in the network. Conclusion Cattle trade network analysis indicated a pathway along which T. b. rhodesiense could spread northwards from eastern Uganda. Targeted T. b. rhodesiense surveillance and control in eastern Uganda, through enhanced public-private partnerships, would serve to limit its spread.